A Study to Evaluate Diosgenin in Laghu gokshur T terrestries and Brihat gokshur Pedalium murex by HPTLC Method - Kalyani, Renuka (International Journal of Pharmaceutical & Biological Archive, 2012)
A Study to Evaluate Diosgenin in Laghu gokshur T terrestries and Brihat gokshur Pedalium murex by HPTLC Method